Facile Synthesis of Phosphonates via Catalyst-Free Multicomponent Reactions in Water - Rostami-Charati, Faramarz; Hossaini, Zinatossadat (Synlett, 2012)
Stable derivatives of phosphonates were prepared using multicomponent reactions of dialkyl acetylenedicarboxylate with 1-(6-hydroxy-2-isopropenyl-1-benzofuran-yl)-1-ethanone or 4-hydroxycoumarin in the presence of trimethyl or triphenyl phosphite in water in good yields.
Keywords: phosphonates; triphenyl phosphate; trimethyl phosphate; triethyl phosphate